Bidirectional association between diabetes mellitus and inflammatory periodontal disease. A review - Stanko, Peter; Izakovicova Holla, Lydie (Biomedical papers, 2014)
Background: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. The abnormal glucose metabolism results from defects in insulin production or insulin action, or both. For decades, it was suspected that diabetes contributed to poorer oral health and the increased frequency of periodontitis. More recently it was found that periodontitis could adversely affect glycemic control in diabetics. This review focuses on the bidirectional relationship between diabetes mellitus and periodontitis.Methods and Results: A review of the literature on periodontal disease in diabetes using the following key words: periodontitis/periodontal disease and diabetes mellitus, hyperglycemia/glycemic control.Conclusions: There is strong evidence for an association between diabetes mellitus and inflammatory periodontal disease. Diabetes mellitus increases the risk for and severity of periodontitis, and periodontal diseases can aggravate insulin resistance and affect glycemic control. Periodontal treatment improves glycemic control in type 2 diabetics; control of periodontal infection is not only important for oral health, it may also improve overall health.
Keywords: diabetes mellitus; periodontitis; hyperglycemia; glycemic control; periodontal treatment